2017
DOI: 10.1097/inf.0000000000001682
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study of a Fully Liquid DTaP-IPV-HB-PRP-T Hexavalent Vaccine for Primary and Booster Vaccinations of Healthy Infants and Toddlers in Latin America

Abstract: These results confirm the suitability of the fully liquid DTaP-IPV-HB-PRP-T vaccine for primary and booster vaccination of infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 18 publications
3
54
0
1
Order By: Relevance
“…The results confirm good antibody persistence up to preschool age following a primary series of the DTaP-IPV-HB-PRP T vaccine with a booster in the second year of life, even following the less immunogenic 6, 10, 14 week infant primary series schedule. Although it is not possible to fully assess any potential impact of the coadministered vaccines in the two studies, the antibody responses post-primary series, pre-booster, and postbooster 16,20,24 are aligned with results from a wide range of studies evaluating the immunogenicity of the DTaP-IPV-HB-PRP~T vaccine in a range of schedules, countries, and with and without coadministered vaccines. [13][14][15][17][18][19][21][22][23] It is therefore unlikely that there would be a clinically important effect of the coadministered vaccines on antibody persistence at 3.5 and 4.5 y of age.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results confirm good antibody persistence up to preschool age following a primary series of the DTaP-IPV-HB-PRP T vaccine with a booster in the second year of life, even following the less immunogenic 6, 10, 14 week infant primary series schedule. Although it is not possible to fully assess any potential impact of the coadministered vaccines in the two studies, the antibody responses post-primary series, pre-booster, and postbooster 16,20,24 are aligned with results from a wide range of studies evaluating the immunogenicity of the DTaP-IPV-HB-PRP~T vaccine in a range of schedules, countries, and with and without coadministered vaccines. [13][14][15][17][18][19][21][22][23] It is therefore unlikely that there would be a clinically important effect of the coadministered vaccines on antibody persistence at 3.5 and 4.5 y of age.…”
Section: Discussionmentioning
confidence: 99%
“…Phase III, randomized, observer-blind, controlled, primary vaccination and booster clinical studies that are reported elsewhere were conducted separately in South Africa (Study 1) 16,24 and Colombia and Costa Rica (Study 2). 20 In Study 1, participants in South Africa who had not received standalone HB vaccine at birth were randomized to receive a 6, 10, 14 week primary series of either DTaP-IPV-HB-PRP~T or DTwP/PRP~T + HB + OPV, and a third group of participants who had received a standalone HB vaccine at birth received a 6, 10, 14 week primary series of DTaP-IPV-HB-PRP~T; 16 all participants were to receive a booster vaccination of the same vaccine-(s) administered in the primary series, co-administered with measles, mumps, rubella, and varicella vaccines (MMR-V). 24 In Study 2, all participants in Colombia and Costa Rica received a standalone HB vaccination at birth and were randomized to receive a primary series of either DTaP-IPV-HB-PRP~T or DTaP-HB-IPV//PRP-T at 2, 4, 6 months of age coadministered with pneumococcal (PCV) 7 vaccine (2, 4, 6 months) and rotavirus vaccine (2 and 4 months); in the second year of life, participants who had received DTaP-IPV-HB-PRP~T in the primary series were randomized to receive a booster of DTaP-IPV-HB-PRP~T or DTaP-HB-IPV//PRP-T, and those who had received a primary series of DTaP-HB-IPV//PRP-T were to receive a booster of DTaP-IPV-HB-PRP~T (booster vaccines were co-administered with PCV7; additionally, MMR-V and PCV13 vaccines were available at 15 months of age in Costa Rica, but not in Colombia, in accordance with the national recommendations).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 3 more Smart Citations